Cloning and characterization of a novel endothelin receptor subtype in the avian class - Lecoin, Laure (The National Academy of Sciences, 1998)
Endothelin 3 (EDN 3) and the endothelin receptor B (EDNRB) are involved in the development of neural crest and particularly of the melanocytes and the enteric nervous system. We reported previously that the avian EDNRB gene is expressed in the neural fold before crest cell migration and later on in all the neural crest derivatives except, at any developmental stage, in the melanocytic lineage. However, quail melanoblasts proliferate in response to EDN 3 stimulation in vitro. These observations prompted us to search for another type of endothelin receptor (EDNR). We report here the cloning by reverse transcriptase–PCR of an avian cDNA encoding a subtype of EDNR, which we have called EDNRB2, because its deduced amino acid sequence is more closely related to that of EDNRB than to either the mammalian EDNRA or to the Xenopus EDNRC. Its expression pattern differs from that of the “classical” avian EDNRB because it is strongly expressed in melanoblasts and melanocytes. EDNRB2 transcripts are also abundant in the liver and kidney. Our pharmacological studies showed that EDNRB2 binds with similar affinity to EDN 1, EDN 2, and EDN 3, further confirming that this receptor belongs to the B type, although it displays a low affinity for sarafotoxin-c, a known EDNRB-selective agonist.